Teaching through virtual tools and its effect on the perception of student satisfaction - Omar Chamorro-Atalaya; Guillermo Morales-Romero; Adrián Quispe-Andía; Darío Villar-Valenzuela; Alicia Jeri-Sandoval; César León-Velarde; Irma Aybar-Bellido (Institute of Advanced Engineering and Science, 2022)
In this context of virtualization, the educational sector has seen the need to make use of technological advances, for this reason it is important to know the perception of students, after having fully adapted distance learning through tools. virtual, which have allowed teachers and students to maintain the pedagogical link at a distance, either through the virtual classroom or through the use of simulation software. In this sense, the objective of this article is to identify the perception of teaching through virtual tools in university students and determine its level of effect or relationship in student satisfaction. This research is approached from a qualitative approach using the Likert measurement method and a content analysis methodology using virtual instruments. The results of the study indicate that 92.9% and 89.3% of the students are satisfied, these results focus on the indicators